Enhancements in Quality of Project Management in the Domain of Information Systems (المجلة الدولية للبحوث العلمية, 2022)
This paper focuses on proposing a quality assurance model for Information Systems Projects Management (IS-PM). This paper presents some important concepts related to this field. It presents the phases and activities of IS-PM. This paper presents a set of proposed steps for achieving each activity of planning ISs projects. Depending on the proposed steps and a combination of statistical techniques, this paper introduces a proposed quality assurance model for IS-PM activities. This proposed model can be used to build an automated software tool. This paper presents a proposed database schema for building such tool.